2018
DOI: 10.1186/s12909-018-1323-y
|View full text |Cite
|
Sign up to set email alerts
|

Research topics and trends in medical education by social network analysis

Abstract: BackgroundAs studies analyzing the networks and relational structures of research topics in academic fields emerge, studies that apply methods of network and relationship analysis, such as social network analysis (SNA), are drawing more attention. The purpose of this study is to explore the interaction of medical education subjects in the framework of complex systems theory using SNA and to analyze the trends in medical education.MethodsThe authors extracted keywords using Medical Subject Headings terms from 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 31 publications
(49 reference statements)
0
31
0
4
Order By: Relevance
“…To this end, BEME reports a 50% increase in the number of reviews undertaken by authors over a recent five-year period. 9 Over the last decade, broad bibliometric reviews of the literature have been undertaken to identify trends in medical education publishing, [10][11][12] recognize the most cited articles in the field, 13 characterize author networks across international borders, 14 and describe associated social media attention. 15,16 While these studies provide important insights into the overall landscape of the medical education literature, they fail to fully illuminate knowledge syntheses and their characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, BEME reports a 50% increase in the number of reviews undertaken by authors over a recent five-year period. 9 Over the last decade, broad bibliometric reviews of the literature have been undertaken to identify trends in medical education publishing, [10][11][12] recognize the most cited articles in the field, 13 characterize author networks across international borders, 14 and describe associated social media attention. 15,16 While these studies provide important insights into the overall landscape of the medical education literature, they fail to fully illuminate knowledge syntheses and their characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we can present science map in medical education by robust evidence. Young (2018) unlike our study found that "Computer-Assisted Instruction," "Personal Sta ng and Scheduling," "User-Computer Interface," "Professional Competency," "Accreditation", "Program Evaluation," and "Educational Measurement," appearing in the eld, he concluded that in the years (2006-2015) medical technological devices have been extensively incorporated into medical practice (29). Our ndings supports the arguments made of Hartzband and Groopman (2009) in regard to turning to the principles of Oslerian medicine embracing the humanistic medicine (31).…”
mentioning
confidence: 47%
“…We argue that based on the educational and scienti c background of the US, the UK, and the Netherlands in pioneering medical education research centers (16) the result of our visualization is rational. Previous SNA studies in medical education also revealed that the United States, the UK, Australia and the Netherlands are the leading countries in scienti c production (14,(28)(29)(30).…”
mentioning
confidence: 97%
“…Pengembangan pendidikan saat ini mewakili peluang untuk meningkatkan kualitas program (Majid, 2016) dan lulusan serta mengarahkannya ke arah globalisasi dan internasionalisasi (Miragaia dan Soares, 2017). Pengaruh desain kurikulum pendidikan dilapangan terhadap pengalaman mahasiswa (Helgevold et al, 2015), dosen, kapasitas lembaga pendidikan (Lawson et al, 2015) merupakan solusi potensial (Ji et al, 2018) untuk mengatasi tantangan pendidikan dimasa depan (Cai, Bo, dan Hsiao, 2018).…”
Section: Latar Belakangunclassified